2020: International year of the nurse and midwife. (2nd December 2019) - Peate, Ian
Abstract : 2020 will be a great year to champion nursing and midwifery, as it is both the bicentenary of Florence Nightingale's birth and The Year of the Nurse and the Midwife, Ian Peate explains